2022
DOI: 10.1002/adfm.202202470
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Multifunctional CuS Nanoparticle‐PEG Composite Soft Hydrogel‐Coated 3D Hard Polycaprolactone Scaffolds for Efficient Bone Regeneration

Abstract: 3D‐printed polycaprolactone (PCL) scaffolds have been extensively studied for application in bone tissue engineering. However, PCL‐based scaffolds with enhanced bioactivity and intelligent delivery capability for bone repair remains challenging. Herein, CuS nanoparticle‐PEG soft hydrogel‐coated 3D hard polycaprolactone scaffolds (denoted as CuS‐PEG‐PCL scaffold) are rationally designed for efficient bone regeneration. CuS nanoparticles cross‐linked PEG hydrogel (CuS‐PEG‐hydrogel) endows the PCL‐based scaffold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 75 publications
1
55
0
Order By: Relevance
“…Furthermore, several authors have reported the use of gels for wound healing, bone regeneration, and the treatment of inflammatory diseases [ 40 , 41 , 42 , 43 , 44 ]. In this study, the enhanced metabolic activity induced by the ALAD-PDT protocol may suggest a new mechanism for fibroblast and osteoblast proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, several authors have reported the use of gels for wound healing, bone regeneration, and the treatment of inflammatory diseases [ 40 , 41 , 42 , 43 , 44 ]. In this study, the enhanced metabolic activity induced by the ALAD-PDT protocol may suggest a new mechanism for fibroblast and osteoblast proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…It was experimentally demonstrated that exosomes enhanced the recruitment of chondrocytes and accelerated cartilage repair. Furthermore, it is feasible to improve the performance of SF-based biomaterials for cartilage/osteochondral repair by loading a variety of nanoparticles (NPs) 189 , 190 . For instance, Li et al prepared SF hydrogels containing BMP-2/TGF-β1@CS NPs 191 .…”
Section: The Application Of Sf-based Biomaterials For Cartilage/osteo...mentioning
confidence: 99%
“…For example, copper is used in PET scanning as a radiotracer agent in cancer diagnostics, and 64CuCl 2 has successfully passed clinical studies demonstrating its diagnostic potential [ 56 ]. Several studies successfully implemented copper for efficient bone regeneration [ 57 ] and anti-inflammatory therapy [ 58 ]. Copper-based nanoparticles also found their place in chemodynamic [ 59 ] and photothermal therapy [ 60 ].…”
Section: Therapeutic Effects Of Copper-based Compounds and Nanocarriersmentioning
confidence: 99%